PENYELENGGARAAN PEMBELAJARAN VOKASI BERDASARKAN MINAT PESERTA DIDIK PADA MATA PELAJARAN KETERAMPILAN FUNGSIONAL PAKET C - Ivo Yani (Jurnal Ilmiah Visi, 2018)
The package C equality education has the distinctiveness of entrepreneurship skills that are put in the functional skills subjects. During this time, the selection of the vocational types (skills) is determined by the package C manager and without the certificate of competence even though the vocational types can be determined based on the student’s interests through the Rothwell Miller Interest Blank (RMIB) test. After completing the competency tests, the graduate students can obtain the competency certificates from the Competence Certification Institutiton (LSK). This study aims to investigate (1) the students’ interest in vocational learning and (2) vocational learning outcomes in package C’s functional skills subjects. The research was conducted to the 26 research subjects of the 6th level of 2nd advanced competency degree in four PKBM at North Sumatra from August to October 2017. In order to seek out the field validation, the quasi experimental design method with pretest and post-test was used. The data collection instrumentswere in the form of tests with 15 items of multiple choice questions. The program significance was tested with the correlated t-test. The finding showed that the value of the t > ttable was (7.01> 2.06). Therefore, it could be concluded that there was a significant difference in values obtained by the students from before and after participating in sewing learning at a 5% significance level. Thus, in determining the vocational interest, the students should pay attention to the availability of the competency test places. References Badan Pengembangan Sumber Daya Manusia Pendidikan dan Kebudayaan dan Penjaminan Mutu Pendidikan.(2013). Pedoman peminatan peserta didik. Diakses melalui http://bk.fip.uny.ac.id/sites/ psikologi-pendidikanbimbingan.fip.uny.ac.id/files/PEDOMAN%20PEMINATAN%20SMA-SMK.pdf Departemen Pendidikan Nasional. (2003). Undang-Undang Republik Indonesia no. 20 tentang sistem pendidikan nasional. Jakarta. Departemen Pendidikan Nasional. (2005). Peraturan pemerintah no. 19 tentang standar nasional pendidikan. Jakarta. Direktorat Pembinaan Kursus dan Pelatihan. (2015). Kurikulum kursus dan pelatihan tata busana jenjang 2 dan 3 berbasis kerangka kualifikasi nasional Indonesia. Jakarta. Djamarah, S. B. (2008). Psikologi belajar. Jakarta: PT. Rineka Cipta. Heri, P. (1998). Pengantar perilaku manusia. Jakarta: EGC. Peraturan Menteri Pendidikan Nasional Nomor 14 Tahun 2007 tentang Standar Isi untuk Program Paket A, Program Paket B, dan Program Paket C. Peraturan Menteri Pendidikan Nasional Nomor 70 Tahun 2008 tentang Uji Kompetensi Bagi Peserta Didik Kursus dan Pelatihan dari Satuan Pendidikan Nonformal atau Warga Masyarakat yang Belajar Mandiri. Pusat Data dan Statistik Pendidikan dan Kebudayaan. (2016). Ikhtisar data pendidikan 2015/2016. Jakarta: Kemendikbud. Rothwell. (1947). Tes RMIB. Diakses melalui http://file.upi.edu/Direktori/FIP/JUR._PSIKOLOGI/195010101980022-SITI_WURYAN_INDRAWATI/TES_RMIB.pdf. Slameto. (2003). Belajar dan faktor-faktor yang mempengaruhinya. Jakarta: PT. Rineka Cipta.